Analisis Sebaran Jasa Ekosistem Penyediaan Pangan dan Air di Daerah Karst (Studi Kasus Kabupaten Buton Tengah) - La Baco S; Kahirun Kahirun; Zulkarnain Zulkarnain; Albasri Albasri (University of Halu Oleo, 2020)
The karst area is the dominant ecosystem in the area of Central Buton District where around 80 percent is a stretch of karst. This objectives of the study was to analyze the ability of ecosystems to provide food and water and its distribution spatially in Central Buton District. This research was conducted through a study of ecoregion characteristics, including data on landscape, natural vegetation types and land cover. In addition, population data, water availability, food availability and administrative data in Central Buton District were collected. Data analysis includes the calculation of ecosystem service indexes, spatial distribution of ecosystem service indices and indicative status of the carrying capacity of food and water. The average index of environmental services for food supply in the Karst area of Central Buton District was 2.52 with a low category, while the index of environmental services for water supply was lower at 1.96 with also a low category. Food service ecosystem index with a low category dominates Central Buton District with an area of 50,286.63 hectares (60.08%) and a medium category of 26,695.97 hectares (31.89%). Water supply ecosystem services index is very low to low with an area of 54,849.99 hectares (65.53%) and 24,551.24 hectares (29.33%). The overall carrying capacity of food and water in Central Buton District is still a surplus. The area of food surplus in the region reached 66,977.53 hectares (80.02%) and the total food surplus was 30,453,510,374 kcal. The total area of water surplus in Central Buton District is 81,291 hectares (97.12%) with a total surplus of 367,826,651 m3/year.Keywords: carrying capacity, ecoregion, ecosystem service index, karst area. AbstrakKawasan karst merupakan ekosistem dominan di wilayah Kabupaten Buton Tengah dimana sekitar 80 persen merupakan hamparan karst. Penelitian ini bertujuan untuk menganalisis kemampuan ekosistem menyediakan pangan dan air serta distribusinya secara spasial di Kabupaten Buton Tengah. Penelitian ini dilakukan melalui kajian karakteristik ekoregion, mencakup data bentang lahan, tipe vegetasi alami dan tutupan lahan. Selain itu dilakukan pengumpulan data kependudukan, ketersediaan air, ketersediaan pangan dan data administrasi Kabupaten Buton Tengah. Analisis data meliputi perhitungan indeks jasa ekosistem, sebaran spasial indeks jasa ekosistem dan status indikatif daya dukung pangan dan air. Rerata indeks jasa lingkungan penyediaan pangan Kawasan Karst Kabupaten Buton Tengah adalah 2,52 dengan kategori rendah, sementara itu indeks jasa lingkungan penyediaan air lebih rendah yakni 1,96 dengan kategori juga rendah. Indeks jasa ekosistem penyediaan pangan dengan kategori rendah mendominasi Kabupaten Buton Tengah dengan luas 50.286,63 hektar (60.08 %) dan kategori sedang seluas 26.695,97 hektar (31,89 %). Indeks jasa ekosistem penyediaan air kategori sangat rendah sampai rendah dengan luas masing-masing 54.849,99 hektar (65,53 %) dan 24.551,24 hektar (29,33 %). Status daya dukung pangan dan air Kabupaten Buton Tengah secara keseluruhan masih surplus. Luas daerah surplus pangan di wilayah tersebut mencapai 66.977,53 hektar (80,02 %) dan total surplus pangan sebanyak 30.453.510.374 kkal. Luas daerah surplus air Kabupaten Buton Tengah adalah 81.291 hektar (97,12 %) dengan total surplus sebanyak 367.826.651 m3/tahun..Kata Kunci: daya dukung, ekoregion, indeks jasa ekosistem, kawasan karst, sebaran spasial.